1996
DOI: 10.1007/bf02230359
|View full text |Cite
|
Sign up to set email alerts
|

Circulating intercellular adhesion molecule 1 in rheumatoid arthritis — Relationship to systemic vasculitis and microvascular injury in nailfold capillary microscopy

Abstract: Intercellular adhesion molecule-1 (ICAM-1) is a membrane bound molecule that plays an important role in the pathogenic inflammatory responses observed in vasculitis. The aim of this study was to determine whether levels of soluble ICAM-1 sICAM-1) shedding into the circulation reflect the vascular injury found in nailfold capillaroscopy as well as systemic vasculitis in RA patients. We determined serum levels of sICAM-1 and soluble interleukin-2 receptor (sIL-2R) by an enzyme-linked immunosorbent assay in 79 RA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 31 publications
2
24
0
Order By: Relevance
“…This is in agreement with previous papers [5,6] whereas other studies have reported elevated levels in this condition [7,8]. Our RA patients were older than the SpA patients and controls, but Cush et al [4] and Kuryliszyn-Moskal et al [8] did not find a correlation between slCAM-1 and age in RA.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This is in agreement with previous papers [5,6] whereas other studies have reported elevated levels in this condition [7,8]. Our RA patients were older than the SpA patients and controls, but Cush et al [4] and Kuryliszyn-Moskal et al [8] did not find a correlation between slCAM-1 and age in RA.…”
Section: Discussionsupporting
confidence: 94%
“…In rheumatoid arthritis (RA), several studies have reported normal [5,6] or elevated levels of sICAM-1 [4,7] with sometimes a weak correlation with disease activity [4] or extra-articular features such as vasculitis [5,8]. In a previous study [9] we found an increased expression of LFA-1 on the surface of granulocytes in spondylarthropathies and LFA-1 expression correlated with total IgA levels in the serum of these patients.…”
mentioning
confidence: 89%
“…Our observations are in agreement with the studies performed in adult RA patients in whom significantly higher levels of sICAM-1 were found in RA patients with clinical signs of systemic vasculitis as compared with those RA patients without clinically apparent vascular involvement. Although no significant correlation between sICAM-1 levels and the capillaroscopy findings were found, in the majority (75%) of the RA patients with severe vascular changes in capillaroscopy, sICAM-1 levels exceeded normal cut off value [23].…”
Section: Discussionmentioning
confidence: 68%
“…CX3CL1 levels are diminished in RV patients successfully treated with glucocorticoids and other immunosuppressive drugs. The c o r r e l a t i o n b e t w e e n C X 3 C L 1 l e v e l s a n d I C A M -1 e x p r e s s i o n i n R V p a t i e n t s s u g g e s t s endothelial damage and/or vascular inflammation (Blann et al 1995;Boehme et al 1996;Kuryliszyn-Moskal et al 1996). The higher CX3CL1 levels observed in RV patients compared with RA or extraarticular manifestation (EAM)-RA patients may be an indicator of undiagnosed vasculitis in RA patients.…”
Section: Cx3c Chemokine 431 Cx3cl1mentioning
confidence: 99%
“…The ICAM-1 protein, TNF-, and E-selectin are expressed in ECs and perivascular mononuclear cells in areas of microvascular damage in the salivary glands of RV patients (Flipo et al 1997). Furthermore, RV patients have elevated levels of sICAM-1 (Voskuyl et al 1995;Kuryliszyn-Moskal, Bernacka et al 1996;Witkowska et al 2003). In addition, Voskuyl et al (Voskuyl, Martin et al 1995) demonstrated the involvement of ICAM-3 and ICAM-1 in patients with RV.…”
Section: Icam-1mentioning
confidence: 99%